Uso de interfaces cérebro máquina para avaliação da fruição artística - Rocha Filho, Edvaldo de Vasconcelos Vieira da (2023)
The objective of this dissertation is to present the development of an artistic enjoyment evaluation system using neural waves through electroencephalograms (EEG). This method is already used to check the most varied possible conditions, for example attention and relaxation. In this research a mixture of waves was used, which were responsible for identifying which work of art caught the users' attention the most, being necessary to use the crossing of the readings of two or more waves for a better interpretation. The experiment used a commercial model EMOTIV INSIGHT headset and a basic mid-range computer to process the data obtained from the various types of waves read, such as Alpha, Beta, Gamma, and Theta. The expectation is that the information said by the user in a test prior to reading the waves with the headset will be similar to the wave data obtained when exposed to the artwork. The evaluation parameter models used was the Design Science Research, with the focus of the study in iteration of the brain with the computer, that is, the Computer Brain Interface (CBI) since it best fits the criteria we established for analysis, the example of one of these criteria is the perception when individuals are exposed to works of art, because this analysis of exposure is not a deterministic factor, having a deductive and inductive character. In this way, the need arises to understand the relationship of what the individual informs prior to the reading of the neural waves with the data after the reading. The result obtained at the end of the research demonstrates that the individuals studied obtained a greater number of interaction peaks, that is, a greater interest in works of art. This fact implies that the more stimuli an individual has, the greater his or her attachment to the work, regardless of the authorship of these works. In the research we compared works ranging from Van Gogh to electronic handicrafts by unknown artists, which provided a greater amount of the latter because of the use of touch in the perception of the stimuli. The impact of this research is that we can demonstrate that the greater the stimuli, the greater the users' immersion in the artwork. Thus, we can detect if they are really interested or even connected to the artwork by its visual context or touch, instead of just being attached to it because the author is a famous artist, thus making the evaluation of artistic enjoyment much closer to the artwork and not only to the historical context of the artist. Such findings may even lead to new, more immersive art shows in the future, capturing and "holding" the individual's attention to what is being presented.